Selective generation of Ag interstitial defects in Te-rich Bi2(Te, Se)3 using Ag nanoparticles causing significant improvement in thermoelectric performance. (February 2018) - Kim, Cham; Jung, Su Yeol; Lopez, David Humberto; Kim, Dong Hwan; Kim, Hoyoung
Abstract: We report significant enhancement in thermoelectric performance of n-type Bi2 (Te, Se)3 prepared via conventional melting process. We deposited chemically synthesized Ag nanoparticles onto Te-rich Bi2 (Te, Se)3 and sintered the resulting substance to obtain a bulk product. The Ag nanoparticles and excessive Te elements should be converted to interstitial and antisite defects in the product, respectively, which possibly interacted to vary thermoelectric transport properties of the product. We endeavored to balance the concentration of the defects to optimize the properties, and thus we strengthened phonon glass electron crystal characteristic of the product, resulting in the improvement in thermoelectric performance. Graphical abstract: